Exploring gut microbiota and metabolite alterations in patients with thyroid-associated ophthalmopathy using high-throughput sequencing and untargeted metabolomics - Zhang, Xiran; Dong, Kui; Zhang, Xinxin; Kang, Zhiming; Sun, Bin (Frontiers in Endocrinology, 2024)
Introduction: Thyroid-associated ophthalmopathy (TAO) is an autoimmune-driven orbital inflammatory disease. Despite research efforts, its exact pathogenesis remains unclear. This study aimed to characterize the intestinal flora and metabolic changes in patients with TAO to identify the flora and metabolites associated with disease development. Methods: Thirty patients with TAO and 29 healthy controls were included in the study. The intestinal flora and metabolites were analyzed using high-throughput sequencing of the 16S rRNA gene and non-targeted metabolomics technology, respectively. Fresh fecal samples were collected from both populations for analysis. Results:Reduced gut richness and diversity were observed in patients with TAO. Compared to healthy controls, significant differences in relative abundance were observed in patients with TAO at the order level Clostridiales, family level Staphylococcaceae, genus level Staphylococcus, Fournierella, Eubacterium siraeum, CAG-56, Ruminococcus gnavus, Intestinibacter, Actinomyces, and Erysipelotrichaceae UCG-003 (logFC>1 and P<0.05). Veillonella and Megamonas were closely associated with clinical symptoms in patients with TAO. Among the 184 significantly different metabolites, 63 were upregulated, and 121 were downregulated in patients with TAO compared to healthy controls. The biosynthesis of unsaturated fatty acids was the significantly enriched metabolic pathway. Correlation analysis revealed Actinomyces was positively correlated with NAGlySer 15:0/16:0, FAHFA 3:0/20:0, and Lignoceric Acid, while Ruminococcus gnavu was positively correlated with Cer 18:0;2O/16:0; ( 3OH) and ST 24:1;O4/18:2. Conclusion: Specific intestinal flora and metabolites are closely associated with TAO development. Further investigation into the functional associations between these flora and metabolites will enhance our understanding of TAO pathogenesis.